2020
DOI: 10.3390/ijerph17041416
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism Profiles and Anger Responses: The Relevant Role of Self-Esteem in Athletes of Professional Quarries

Abstract: Perfectionism is a multidimensional personality trait characterized by effort and rigidity in setting high personal standards, accompanied by an excessive tendency toward critical assessments, which plays an important role in cognitive, behavioral, and emotional functioning. During adolescence, personality is built on a fundamental pillar—self-esteem—which plays an important role in sports practice when it comes to achieving the best possible performance. Anger has an emotional component that, interpreted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
8
1
1
Order By: Relevance
“…The implications of these findings are unclear in the present context as the study did not aim to address perfectionism and anger; however, these findings could imply that the setting of high standards (regardless of motivation for the standards) could be related to people's reactions to anger inducing situations. Some previous research (Muñoz-Villena et al, 2020) has found that self-esteem, which was not measured in the present set of studies, is also a mediator between perfectionism and anger. Future research that tests these findings further should include a measure of self-esteem, in order to explore this possiblity.…”
Section: Angercontrasting
confidence: 75%
“…The implications of these findings are unclear in the present context as the study did not aim to address perfectionism and anger; however, these findings could imply that the setting of high standards (regardless of motivation for the standards) could be related to people's reactions to anger inducing situations. Some previous research (Muñoz-Villena et al, 2020) has found that self-esteem, which was not measured in the present set of studies, is also a mediator between perfectionism and anger. Future research that tests these findings further should include a measure of self-esteem, in order to explore this possiblity.…”
Section: Angercontrasting
confidence: 75%
“…Therefore, in basketball, the coach’s anger is usually caused by frustration that the game is not going as intended, or by some refereeing decision, and only occasionally when someone treats them badly. In fact, the appearance of anger in sport is more frequent when perceived self-esteem is low [ 45 ]. These data indicate the need to be aware of anger, reflecting on its cause(s), and especially on the behavioural reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has elucidated positive outcomes that are associated with individuals with pure personal standards (e.g., Gong et al, 2017; Muñoz-Villena et al, 2020). In particular, some researchers have found a positive relationship between higher achievement and personal standards (e.g., Sotardi & Dubien, 2019).…”
Section: Known Knowns In Multidimensional Perfectionism Researchmentioning
confidence: 99%